Variation in treatment of acute childhood wheeze in emergency departments of the United Kingdom and Ireland: an international survey of clinician practice. Issue 2 (25th August 2014) - Lyttle, Mark D; O'Sullivan, Ronan; Doull, Iolo; Hartshorn, Stuart; Morris, Ian; Powell, Colin V E
Abstract : Objective: National clinical guidelines for childhood wheeze exist, yet despite being one of the most common reasons for childhood emergency department (ED) attendance, significant variation in practice occurs in other settings. We, therefore, evaluated practice variations of ED clinicians in the UK and Ireland. Design: Two-stage survey undertaken in March 2013. Stage one examined department practice and stage two assessed ED consultant practice in acute childhood wheeze. Questions interrogated pharmacological and other management strategies, including inhaled and intravenous therapies. Setting and participants: Member departments of Paediatric Emergency Research in the United Kingdom and Ireland and ED consultants treating children with acute wheeze. Results: 30 EDs and 183 (81%) clinicians responded. 29 (97%) EDs had wheeze guidelines and 12 (40%) had care pathways. Variation existed between clinicians in dose, timing and frequency of inhaled bronchodilators across severities. When escalating to intravenous bronchodilators, 99 (54%) preferred salbutamol first line, 52 (28%) magnesium sulfate (MgSO4 ) and 27 (15%) aminophylline. 87 (48%) administered intravenous bronchodilators sequentially and 30 (16%) concurrently, with others basing approach on case severity. 146 (80%) continued inhaled therapy after commencing intravenous bronchodilators. Of 170 who used intravenous salbutamol, 146 (86%) gave rapid boluses, 21 (12%) a longer loading dose and 164 (97%) an ongoing infusion, each with a range of doses and durations. Of 173 who used intravenous MgSO4, all used a bolus only. 41 (24%) used non-invasive ventilation. Conclusions: Significant variation in ED consultant management of childhood wheeze exists despite the presence of national guidance. This reflects the lack of evidence in key areas of childhood wheeze and emphasises the need for further robust multicentre research studies.